Characterisation of new diplonemid species via electron microscopy, starvation experiments and immunofluorescence studies - Cimrhanzlová, Kristýna (Jihočeská univerzita, 2020)
The large abundance and diversity of diplonemids in oceans has been overlooked until recently. Diplonemids are now starting to be recognised as an abundant and diverse group of the planktonic community. It is in our best interest to study these fascinating microorganisms to learn more about how they impact the ecosystems of the world's oceans. This thesis is focused primarily on morphological descriptions and determination of the life stages of four newly discovered species.
Characterisation of new diplonemid species via electron microscopy, starvation experiments and immunofluorescence studies
Keywords: diplonemids; morphology; endosymbionts; taxonomy; microscopy; immunofluorescence; species; growth curves; mitochondria; starvation experiments; diplonemids; morphology; endosymbionts; taxonomy; microscopy; immunofluorescence; species; growth curves; mitochondria; starvation experiments